Transforming Building Infrastructure into Communication Systems for Smart City: A Conceptual Analysis of Metallic Structures as Antennas - Zain, Nurmayanti; Arifin, Farhan Rezki; Emakarim, Lompo Ramos (Journal La Multiapp, 2025)
The transformation of building infrastructure into intelligent communication systems is a key enabler of smart city development. This paper investigates the feasibility of utilizing metallic structural elements such as steel reinforcement bars, hollow sections, and galvanized steel as embedded antenna within building frameworks. To provide validated evidence, this work incorporates full-wave electromagnetic simulations using Ansys HFSS to analyze resonance behavior, impedance matching, radiation patterns, and gain performance in the sub-GHz band, particularly around 700 MHz for IoT applications. The simulation results demonstrate that selected building materials can achieve stable resonance and nearly omnidirectional radiation characteristics, with realized gains up to 0.47 dBi and bandwidths sufficient for LPWAN technologies such as NB-IoT and LoRaWAN. These findings confirm the dual functionality of structural metals, offering both mechanical strength and communication capability. The study provides a validated basis for future experimental prototyping and integration of antenna- embedded infrastructures in smart building environments.